Development and utility of a clinical research informatics application for participant recruitment and workflow management for a return of results pilot trial in familial hypercholesterolemia in the Million Veteran Program - Brunette, Charles A; Yi, Thomas; Danowski, Morgan E; Cardellino, Mark; Harrison, Alicia; Assimes, Themistocles L; Knowles, Joshua W; Christensen, Kurt D; Sturm, Amy C; Sun, Yan V; Hui, Qin; Pyarajan, Saiju; et al. (JAMIA open, 2024)
Objective The development of clinical research informatics tools and workflow processes associated with re-engaging biobank participants has become necessary as genomic repositories increasingly consider the return of actionable research results. Materials and Methods Here we describe the development and utility of an informatics application for participant recruitment and enrollment management for the Veterans Affairs Million Veteran Program Return Of Actionable Results Study, a randomized controlled pilot trial returning individual genetic results associated with familial hypercholesterolemia. Results The application is developed in Python-Flask and was placed into production in November 2021. The application includes modules for chart review, medication reconciliation, participant contact and biospecimen logging, survey recording, randomization, and documentation of genetic counseling and result disclosure. Three primary users, a genetic counselor and two research coordinators, and 326 Veteran participants have been integrated into the system as of February 23, 2023. The application has successfully handled 3367 task requests involving greater than 95 000 structured data points. Specifically, application users have recorded 326 chart reviews, 867 recruitment telephone calls, 158 telephone-based surveys, and 61 return of results genetic counseling sessions, among other available study tasks. Conclusion The development of usable, customizable, and secure informatics tools will become increasingly important as large genomic repositories begin to return research results at scale. Our work provides a proof-of-concept for developing and using such tools to aid in managing the return of results process within a national biobank. Lay Summary The Million Veteran Program Return Of Actionable Results (MVP-ROAR) Study is exploring the acceptance and feasibility of returning genetic results related to familial hypercholesterolemia (family-related high blood cholesterol) to participants in the US Department of Veterans Affairs Million Veteran Program. We developed a user-friendly computer application that can be used by our research team to help manage the process for re-contacting, re-consenting, and enrolling MVP participants into the MVP-ROAR Study. The computer application includes multiple modules that allow our research team to track where participants are in the return of results process as well as enter important operational and study data, including the recording of information related to health record reviews, recruitment and enrollment information, participant surveys, and genetic counseling sessions. Our experience building a computer system for managing a return of results process may be important to future return of results initiatives in MVP and can be used as an example by other large biobanks that would like to return genetic results to their participants.